2021
DOI: 10.3390/w13030354
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Arsenic and Iron Removal Plants (AIRPs) for Groundwater Treatment in Rural Areas of Southwest Bangladesh

Abstract: Arsenic (As) removal plants were installed in As-endemic areas of Bangladesh to remove As from well water. In many cases, these removal plants did not perform satisfactorily. This study evaluated the efficiency of 20 As and iron (Fe) removal plants (AIRPs) during pre- and post-monsoon conditions in rural Bangladesh. Results revealed that As removal efficiencies ranged from 67% to 98% and 74 to 93% during the pre- and post-monsoons periods, respectively. In the post-monsoon season As removal at individual AIRP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The Pleistocene aquifer which is a deeper aquifer is not a safe alternative source as it was observed that deeper aquifers contain less As, but nonetheless may cause lifetime cancer risks to children. For this reason, cost-effective arsenic iron removal plants (AIRPs) (Rahman et al 2021b) and SONO lters (one type of e cient As-Fe removal plant) can be installed in school premises to reduce As and Fe from raw drinking water to a safer level.…”
Section: Declarations Acknowledgementmentioning
confidence: 99%
“…The Pleistocene aquifer which is a deeper aquifer is not a safe alternative source as it was observed that deeper aquifers contain less As, but nonetheless may cause lifetime cancer risks to children. For this reason, cost-effective arsenic iron removal plants (AIRPs) (Rahman et al 2021b) and SONO lters (one type of e cient As-Fe removal plant) can be installed in school premises to reduce As and Fe from raw drinking water to a safer level.…”
Section: Declarations Acknowledgementmentioning
confidence: 99%